Electrolytes Enriched by Crown Ethers for Lithium Metal Batteries. (12th July 2020) - Wang, Huaping; He, Jian; Liu, Jiandong; Qi, Shihan; Wu, Mingguang; Wen, Jie; Chen, Yanan; Feng, Yuezhan; Ma, Jianmin
Abstract: Lithium (Li) metal battery is considered the most promising next‐generation battery due to its low potential and high theoretical capacity. However, Li dendrite growth causes serious safety problems. Herein, the 15‐Crown‐5 (15‐C‐5) is reported as an electrolyte additive based on solvation shell regulation. The strong complex effect between Li + ion and 15‐C‐5 can reduce the concentration of Li ions on the electrode surface, thus changing the nucleation, and repressing the growth of Li dendrites in the plating process. Significantly, the strong coordination of Li + /15‐C‐5 would be able to make them aggregate around the Li crystal surface, which could form a protective layer and favor the formation of a smooth and dense solid electrolyte interphase with high toughness and Li + ion conductivity. Therefore, the electrolyte system with 2.0 wt% 15‐C‐5 achieves excellent electrochemical performance with 170 cycles at 1.0 mA cm −2 with capacity of 0.5 mA h cm −2 in symmetric Li|Li cells. The obviously enhanced cycle and rate performance are also achieved in Li|LiNi0.6 Co0.2 Mn0.2 O2 (NCM622) full cells. The 15‐C‐5 demonstrates to be a promising additive for the electrolytes toward safe and efficient Li metal batteries. Abstract : Owing to the strong coordination ability, 15‐Crown‐5 (15‐C‐5) ether can coordinate with Li + to form a Li + /15‐C‐5 protective layer in Li surface and favor the formation of smooth and dense solid electrolyte interphase films with high Li + conductivity. This is found to be effective to enable high‐performance electrolytes for Li metal batteries with a life span of 170 cycles.